2020
DOI: 10.1242/dmm.045559
|View full text |Cite
|
Sign up to set email alerts
|

Duchenne muscular dystrophy (DMD) cardiomyocyte-secreted exosomes promote the pathogenesis of DMD-associated cardiomyopathy

Abstract: Cardiomyopathy is a leading cause of early mortality in Duchenne muscular dystrophy (DMD). There is a need to gain a better understanding of the molecular pathogenesis for the development effective therapies. Exosomes (exo) are secreted vesicles and exert effects via their RNA, lipid and protein cargo. The role of exosomes in disease pathology is unknown. Exosomes derived from stem cells have demonstrated cardioprotection in the murine DMD heart. However, it is unknown how the disease status of the donor cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 94 publications
0
20
0
Order By: Relevance
“…A recent paper from Gartz et al. ( 2020 ), showed that GW4869 treatment to reduce exosome release (by neutral sphingomyelinase [nSMase] inhibition) in mdx mice (a popular model of DMD) was protective against cardiac stress, which authors attributed to miR cargo. In line with this, Matsuzaka et al.…”
Section: Musculoskeletal Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…A recent paper from Gartz et al. ( 2020 ), showed that GW4869 treatment to reduce exosome release (by neutral sphingomyelinase [nSMase] inhibition) in mdx mice (a popular model of DMD) was protective against cardiac stress, which authors attributed to miR cargo. In line with this, Matsuzaka et al.…”
Section: Musculoskeletal Pathologymentioning
confidence: 99%
“…Research on EV biology has suggested that EVs may be used to aid early DMD diagnosis, as well as our understanding of the mechanistic underpinnings of the disease (Coenen-Stass et al, 2017), but their contents and function are still under investigation (Rogers et al, 2019). A recent paper from Gartz et al (2020), showed that GW4869 treatment to reduce exosome release (by neutral sphingomyelinase [nSMase] inhibition) in mdx mice (a popular model of DMD) was protective against cardiac stress, which authors attributed to miR cargo. In line with this, Matsuzaka et al (2020) showed that ablation of nSMase2/Smpd3 gene in mice with a mdx background decreased muscle inflammation and improved functionality.…”
Section:  Skeletal Musclementioning
confidence: 99%
“…The CTD of dystrophin interacts with various cytosolic proteins, such as dystrobrevin or syntrophins (Syn). Syntrophins recruit sodium channels and signaling molecules, such as neuronal nitric oxide synthase (nNOS) microvasculature, and innervation; however, signalingrelated topics, such as noncoding RNAs or exosomes, are omitted because they have been previously reviewed indepth [67][68][69]. The involvement of dystrophins in cell signaling and communication opens new therapeutic avenues as either adjuvants or stand-alone approaches.…”
Section: Molecular Background Of Duchenne Muscular Dystrophymentioning
confidence: 99%
“…These changes are probably due to dysfunction in the Pink1/Parkin1 pathway, which regulates the process of cleaning cells from nonfunctional mitochondria [222]. Affected cardiomyocytes also release exosomes containing miRNAs, which have been found to aggravate DMD pathogenesis [223]. Furthermore, enhanced Tgfβ1 signaling in coronary adventitial cells was identified as a factor that induces fibrotic changes.…”
Section: Cell Signaling In the Heartmentioning
confidence: 99%
“…However, subsequent studies have described and fully characterised cardiac abnormalities in novel mouse ( Wong et al, 2020 ), rat ( Szabó et al, 2021 ) and porcine ( Stirm et al, 2021 ) models of DMD. In vitro approaches are also valuable, as demonstrated by a recent study showing that exosomes secreted by DMD cardiomyocytes differentiated from human stem cells exacerbated the vulnerability of DMD cardiomyocytes to stress ( Gartz et al, 2020 ). This expanding toolkit for exploring DMD-associated cardiac impairment will potentiate research in this field and propel clinical progress.…”
mentioning
confidence: 99%